ANALISA PENGARUH WAKTU TUNGGU KAPAL TERHADAP BIAYA LOGISTIK DI TERMINAL PETI KEMAS MAKASSAR - Ramadani, Alya; Virandika, Cece (Riset Sains dan Teknologi Kelautan, 2022)
Logistics costs are a factor that greatly affects the competitiveness of companies and countries. these logistics costs adds to the cost of materials and products and is often a problem for both exporters and importers. The problem is the logistical costs associated with staying at the port to accommodate goods, which in turn increases logistics costs. There are several factors that affect the waiting time of the ship. Specifically, the process of loading and unloading containers, the capacity of the stacking area, the loading and unloading facilitiesrequired by each terminal operator, as well as the density of loading and unloading flows, etc. The method used in This research is a qualitative method with a descriptive approach: searching, reading, and collectingresearch related to books, articles, and journals. Dwelling Time Problems at Indonesian Ports 4 (Persero) Makassar Container Terminal Branch is vulnerable to additional fees and bribes. Solution for overcoming dwelling time at Port of Indonesia 4 (Persero) Makassar Container Terminal Branch will serving activities outside Blegen, increasing loading and unloading capacity of equipment, extending operating hours and reducing the port to increase its role